If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5=-4(Y+3)
We move all terms to the left:
-5-(-4(Y+3))=0
We calculate terms in parentheses: -(-4(Y+3)), so:We get rid of parentheses
-4(Y+3)
We multiply parentheses
-4Y-12
Back to the equation:
-(-4Y-12)
4Y+12-5=0
We add all the numbers together, and all the variables
4Y+7=0
We move all terms containing Y to the left, all other terms to the right
4Y=-7
Y=-7/4
Y=-1+3/4
| 3(2x-7)=(-33) | | -60+8x=14x+102 | | 9−−18÷−2=x | | 3(y+1)=7.5 | | 3(p+7)=9 | | Y=-0.02d²+2.6d-66.5 | | 2^t-12(12t)+32=0 | | v^2=10 | | 15y=60-18× | | (3x)+21=3(x+7) | | 5(4^x)=30 | | 3-4y=5y-15 | | 9*5^(2x+1)=27 | | 64*(0.9)^x=0 | | 0.9^x=64 | | 7x+8=2x+17 | | 3(1.5x+9)=-31.5 | | 7+-x=-10 | | 3x+14=9x-3 | | 24/33=32/f | | -0.9p+3.2=-1.17p | | -2x+17=45 | | -2x-17=45 | | 3f-2=5f+13 | | 38-3x=14 | | -2x+12=45 | | 13=5/2x | | 30/55=18/t | | -7x+13=-27 | | 90+2x=5x+21 | | 902x=5x+21 | | 90x+2x=5x+21 |